2007
DOI: 10.3758/bf03196831
|View full text |Cite
|
Sign up to set email alerts
|

Conflict monitoring and feature overlap: Two sources of sequential modulations

Abstract: Recent findings demonstrating that the Simon effect diminishes when the preceding trial is a noncorresponding trial led researchers to develop two alternative accounts. The conflict monitoring account argues that the automatic activation from stimulus location information is under the regulation of a control mechanism, which adjusts the level of activation depending on conflict in the preceding trial. In contrast, the feature integration account holds that sequential modulations of the Simon effect can be attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
86
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 23 publications
(32 reference statements)
7
86
0
Order By: Relevance
“…When Mayr and colleagues analysed only complete alternation trials, where both the word and the colour change (e.g., BLUE red followed by GREEN yellow ), the Gratton effect QUESTIONING CONFLICT ADAPTATION 21 was eliminated. Subsequent work has confirmed that removing these stimulus binding biases substantially reduces the Gratton effect, but a significant remaining effect is often observed (e.g., Akçay & Hazeltine, 2007Funes, Lupiáñez, & Humphreys, 2010;Van Gaal, Lamme, & Ridderinkhof, 2010;Verbruggen, Notebaert, Liefooghe, & Vandierendonck, 2006). Thus, binding plays a sizeable role, but is clearly not the whole story (see Egner, 2007 for a review).…”
Section: Grattonmentioning
confidence: 86%
“…When Mayr and colleagues analysed only complete alternation trials, where both the word and the colour change (e.g., BLUE red followed by GREEN yellow ), the Gratton effect QUESTIONING CONFLICT ADAPTATION 21 was eliminated. Subsequent work has confirmed that removing these stimulus binding biases substantially reduces the Gratton effect, but a significant remaining effect is often observed (e.g., Akçay & Hazeltine, 2007Funes, Lupiáñez, & Humphreys, 2010;Van Gaal, Lamme, & Ridderinkhof, 2010;Verbruggen, Notebaert, Liefooghe, & Vandierendonck, 2006). Thus, binding plays a sizeable role, but is clearly not the whole story (see Egner, 2007 for a review).…”
Section: Grattonmentioning
confidence: 86%
“…A typical finding when investigating Simon compatibility effects, for example, is that the size of the Simon effect critically depends on the characteristics of the preceding trial. In particular, the sequential modulation effect reflects the finding that Simon effects in a current trial N are smaller following incompatible trials in N -1 compared to those following compatible trials in N -1 (Akçay & Hazeltine, 2007;Fischer, Dreisbach, & Goschke, 2008;Hommel, Proctor, & Vu, 2004;Notebaert, Soetens, & Melis, 2001;Stürmer, Leuthold, Soetens, Schröter, & Sommer, 2002;Wühr & Ansorge, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have employed designs under which congruent trials occur more often than they would by chancethat is, more often that they would if the relevant and irrelevant attributes of the stimulus were selected independently. In particular, in several recent studies the researchers have used 4-AFC tasks with designs under which congruent trials occur 50% of the time, instead of the 25% that would be expected by chance (e.g., Akçay & Hazeltine, 2007Wendt & Kiesel, 2011); other experiments have used rates of congruence that are even farther from what would be expected by chance, such as 70% congruent trials in a 3-AFC task (e.g., Kerns et al, 2004;Larson, Kaufman, & Perlstein, 2009;Mayr & Awh, 2009). The goal of this observation is to convince the reader that this should not be done; 50% congruent should, instead, be avoided when the task is 4-AFC.…”
Section: Abstract Executive Control Cognitive Control Selective Amentioning
confidence: 99%